2018
DOI: 10.7566/jpsj.87.033701
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Quantum Phase Transition of SrCu2(BO3)2 by High-Pressure and Terahertz Electron Spin Resonance

Abstract: High-pressure and high-field electron spin resonance (ESR) measurements have been performed on a single crystal of the orthogonal-dimer spin system SrCu 2 (BO 3 ) 2 . With frequencies below 1 THz, ESR signals associated with transitions from the singlet ground state to the one-triplet excited states and the two-triplet bound state were observed at pressures up to 2.1 GPa. We obtained directly the pressure dependence of the gap energies, finding a clear firstorder phase transition at P c = 1.85 ± 0.05 GPa. By c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 35 publications
(80 reference statements)
4
49
0
Order By: Relevance
“…At higher pressures they become undetectably weak or shift outside our measurement window (T 1 ). The observed softening of the triplet modes is fully consistent with previous Electron spin resonance(ESR) [27] and inelastic neutron scattering [23] studies, shown as triangles and squares in the figure. The softening of the singlet mode is a new result, since neither ESR nor neutrons are sensitive to singlet-singlet transitions.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…At higher pressures they become undetectably weak or shift outside our measurement window (T 1 ). The observed softening of the triplet modes is fully consistent with previous Electron spin resonance(ESR) [27] and inelastic neutron scattering [23] studies, shown as triangles and squares in the figure. The softening of the singlet mode is a new result, since neither ESR nor neutrons are sensitive to singlet-singlet transitions.…”
supporting
confidence: 90%
“…It can only be driven by a subtle change in the J /J ratio, as assumed in most theoretical studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It takes place long before the exchange constants themselves can be expected to switch sign [27]. It also seems not to be associated with any structural transition, of which we do not observe any obvious signs such as splitting of phonon lines or the appearance of new modes.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…As the high-field ESR measurements observed the excited states very clearly for this system [15], such measurements at high pressure offer a means to investigate this phase transition. Recently, within the field range of 10 T, we revealed that the system undergoes a quantum phase transition at 1.85 GPa [16]. On the other hand, the first excited triplet states cross the ground state at around 25 T at 0 GPa [15].…”
Section: Application To Orthogonal Dimer Spin System Srcu 2 (Bo 3 )mentioning
confidence: 96%
“…We use a transmission technique in our ESR systems and we have developed specially designed piston-cylinder type pressure cells using ceramics inner parts which have good transmittance to millimeter and submillimeter waves. It turned out that the high-pressure and high-field ESR measurement is a good means to explore the pressure-induced phase transition of quantum magnet like SrCu 2 (BO 3 ) 2 [7].…”
Section: Introductionmentioning
confidence: 99%